Research on the Optimization of Brand Communication Paths and Effectiveness Evaluation under the Online Marketing Environment - Gao, Linyuan (Pinnacle Academic Press Proceedings Series, 2026)
With the rapid development of internet technology, online marketing has become a crucial approach for brand communication and value creation. In a complex media environment characterized by fragmentation, interactivity, and personalized consumption, traditional linear communication models are increasingly unable to meet the needs of enterprises seeking sustained brand growth. This paper analyzes the main characteristics of brand communication under the online marketing environment, including multi-platform dissemination, user-generated content, and data-driven targeting. On this basis, it classifies brand communication paths into such categories as official media channels, third-party platforms, social networks, and word-of-mouth diffusion, and constructs an optimized model for brand communication that emphasizes integration, coordination, and feedback loops. Furthermore, the study proposes a multi-dimensional evaluation system to assess communication effectiveness from the perspectives of communication reach, audience engagement, attitude change, conversion behavior, and long-term brand equity. Through theoretical analysis combined with empirical case studies, the research identifies key factors that influence the efficiency of online brand communication and reveals how different paths interact to shape consumer behavior. The findings provide targeted strategic suggestions for enterprises to allocate communication resources more rationally, improve brand influence, and enhance marketing efficiency in the digital environment.